2021
DOI: 10.1007/s11306-020-01761-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profiling of semi‐polar phytochemicals in whole wheat grains (Triticum aestivum) using liquid chromatography coupled with electrospray ionization quadrupole time‐of‐flight mass spectrometry

Abstract: Introduction Wheat (Triticum aestivum) it is one of the most important staple food crops worldwide and represents an important resource for human nutrition. Besides starch, proteins and micronutrients wheat grains accumulate a highly diverse set of phytochemicals. Objectives This work aimed at the development and validation of an analytical workflow for comprehensive profiling of semi-polar phytochemicals in whole wheat grains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…Lignan is a secondary plant metabolite produced by the oxidative coupling of phenylpropane compounds, derived from the shikimic acid biosynthesis pathway and widely distributed in plants as natural polyphenolic compounds. Lignans have a wide range of biological activities, such as antioxidant, antitumor, antibacterial, insecticidal, estrogen‐like, and cardioprotective 35–38 . Lignan is predominantly composed of guaiacyl (G) and syringyl (S) derived from the combinatorial radical–radical coupling of the monolignols coniferyl and sinapyl alcohol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignan is a secondary plant metabolite produced by the oxidative coupling of phenylpropane compounds, derived from the shikimic acid biosynthesis pathway and widely distributed in plants as natural polyphenolic compounds. Lignans have a wide range of biological activities, such as antioxidant, antitumor, antibacterial, insecticidal, estrogen‐like, and cardioprotective 35–38 . Lignan is predominantly composed of guaiacyl (G) and syringyl (S) derived from the combinatorial radical–radical coupling of the monolignols coniferyl and sinapyl alcohol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lignans have a wide range of biological activities, such as antioxidant, antitumor, antibacterial, insecticidal, estrogen-like, and cardioprotective. [35][36][37][38] Lignan is predominantly composed of guaiacyl (G) and syringyl (S) derived from the combinatorial radical-radical coupling of the monolignols coniferyl and sinapyl alcohol, respectively. As radical coupling at the 8-position is favored, coupling with another monolignol radical yields, after rearomatization, a mixture of dehydrodimers with 8-8-, 8-5-, and 8-O-4-linkages.…”
Section: Fragmentation Behaviors Of Lignan Oligomersmentioning
confidence: 99%
“…Flavonoids were the major class of annotated metabolites found as aglycone and glycosylated forms: flavanones (isosakuranin, naringenin, narirutin 4-glucoside, 5,7,4′-trihydroxyflavanone 7-O-arabinosylglucoside, 5-O-β-D-glucosylluteoliflavan-(4 → 8)-eriodictyol), flavones (apigenin, isovitexin 2″-O-glucoside), flavanols (epicatechin, catechin, epigallocatechin 3-gallate, epicatechin 3-gallate, procyanidin B, symplocoside), chalcones (dihydroxy-4-methoxychalcone-4′-O-neohesperid), flavonols (myricetin, kaempferol), and isoflavonoids (gancaonin, isoprunetin, daidzin, ononin). 16,17,43 Hydroxycinnamic acids and their derivatives were the main phenolic acids found, despite the fact that hydroxybenzoic acids have also been detected: caffeic acid, p-coumaric acid and its isomer, sinapic acid, trans-ferulic acid and its isomer (cis-ferulic acid), dihydroxyphenylacetic acid, isomers of diferulic acids, 2,5dihydroxybenzoic acid, dihydrocaffeic, 4-hydroxybenzoic acid, sinapic acid, syringic acid, and caffeoyl glucose. Hydroxycinnamic acids were also found conjugated with quinic acid: chlorogenic acid, feruloylquinic acid, and coumaroylquinic acid.…”
Section: Metabolomics Revealing the Metabolite Diversity Of Cereal Cr...mentioning
confidence: 99%
“…Diferulic acids were previously reported in cereal grains, including rye, sorghum, and wheat. 17,45,47 Furthermore, the metabolomics data was submitted to multivariate data analyses to have an overview of the metabolite distribution in cereal crops and milling fractions. Unsupervised (principal component analysis, PCA; hierarchical clustering analysis, HCA) and supervised (partial least-squares-discriminant analysis, PLS-DA) methods were applied to analyze the data.…”
Section: Metabolomics Revealing the Metabolite Diversity Of Cereal Cr...mentioning
confidence: 99%
“…Whole grain is characterized by the retention of the endosperm, germ, and bran found in whole grain (WG). WG is a good source of dietary fiber, protein, B vitamins, vitamin E, minerals (such as selenium, copper, and magnesium), flavonoids, and polyphenols (14)(15)(16). Numerous studies have shown that they can help to reduce the risk of many diseases, such as overweight (OW)/obesity, cardiovascular disease, type 2 diabetes, intestinal disease, and certain cancers, as compared to refined grains.…”
Section: Introductionmentioning
confidence: 99%